New self-sexing Aedes aegypti strain eliminates barriers to scalable and sustainable vector control for governments and communities in dengue-prone environments - Spinner, Siân A. M.; Barnes, Zoe H.; Puinean, Alin Mirel; Gray, Pam; Dafa’alla, Tarig; Phillips, Caroline E.; Nascimento de Souza, Camila; Frazon, Tamires Fonseca; Ercit, Kyla; Collado, Amandine; Naish, Neil; Sulston, Edward; et al. (Frontiers in Bioengineering and Biotechnology, 2022)
For more than 60 years, efforts to develop mating-based mosquito control technologies have largely failed to produce solutions that are both effective and scalable, keeping them out of reach of most governments and communities in disease-impacted regions globally. High pest suppression levels in trials have yet to fully translate into broad and effective Aedes aegypti control solutions. Two primary challenges to date – the need for complex sex-sorting to prevent female releases, and cumbersome processes for rearing and releasing male adult mosquitoes – present significant barriers for existing methods. As the host range of Aedes aegypti continues to advance into new geographies due to increasing globalisation and climate change, traditional chemical-based approaches are under mounting pressure from both more stringent regulatory processes and the ongoing development of insecticide resistance. It is no exaggeration to state that new tools, which are equal parts effective and scalable, are needed now more than ever. This paper describes the development and field evaluation of a new self-sexing strain of Aedes aegypti that has been designed to combine targeted vector suppression, operational simplicity, and cost-effectiveness for use in disease-prone regions. This conditional, self-limiting trait uses the sex-determination gene doublesex linked to the tetracycline-off genetic switch to cause complete female lethality in early larval development. With no female progeny survival, sex sorting is no longer required, eliminating the need for large-scale mosquito production facilities or physical sex-separation. In deployment operations, this translates to the ability to generate multiple generations of suppression for each mosquito released, while being entirely self-limiting. To evaluate these potential benefits, a field trial was carried out in densely-populated urban, dengue-prone neighbourhoods in Brazil, wherein the strain was able to suppress wild mosquito populations by up to 96%, demonstrating the utility of this self-sexing approach for biological vector control. In doing so, it has shown that such strains offer the critical components necessary to make these tools highly accessible, and thus they harbour the potential to transition mating-based approaches to effective and sustainable vector control tools that are within reach of governments and at risk communities who may have only limited resources.